Cytotoxic and anti-diabetic potential, metabolic profiling and insilico studies of Syzygium cumini (L.) Skeels belonging to family Myrtaceae. Issue 4 (16th February 2022) - Eldin Elhawary, Seham Salah; Elmotyam, Amira kamal Eldin; Alsayed, Doaa kamel; Zahran, Eman Maher; Fouad, Merivat Ahmed; Sleem, Amany Ameen; Elimam, Hanan; Rashed, Mohamed H.; Hayallah, Alaa M.; Mohammed, Anber F.; Abdelmohsen, Usama Ramadan
Abstract: LC-HR-MS-coupled metabolic profiling of the methanol extracts from different parts of Syzygium cumini (L.), which was extensively identified via DNA fingerprinting, led to dereplication of 24 compounds. Cytotoxic investigation highlighted both extracts as the most potent, against both MCF-7 and MDA-231 Cell lines, with IC50 value of 5.86 ± 0.63 µg/ml and against HCT −116 cell line, with IC50 value of 1.24 ± 0.09 µg/ml, respectively. A molecular docking study was performed on the dereplicated compounds, which highlighted myricetin-3-glucoside (7 ), myricitrin (12 ), reynoutrin (15 ) and quercitrin (16 ) as the top scoring ligands within the protein active site (FIH-1). Interestingly, the extracts were significant against streptozotocin-induced diabetes in the order of flowers > seeds > leaves with BGL level of 98.9 ± 4.3, 123.2 ± 4.9 and 132.8 ± 5.9 mg/dl, respectively. The study highlights the health benefits of Syzygium cumini (L.) as a promising cytotoxic source. Graphical Abstract: